Anti-proliferative effect of Trifolium pratense extract on Raji cell line in Burkitt's lymphoma - Morteza Davoodi; Shahriyar Saeediyan; Reza Saghiri; Zahra Zamani; Gholamreza Bakhshi Khaniki (Islamic Azad University, Shahrekord Branch, 2022)
Background & Aim: In folk medicine, red clover (Trifolium pratense) use to treat some diseases such as whooping cough, asthma, eczema, and some ophthalmic dysfunction. Due to its phytoestrogens and antioxidant-rich compounds, it is recommended to alleviate some cancers. This paper was conducted to study the anti-cancer and apoptosis effects of red clover extract (RCE) on the Raji cell line in Burkitt's lymphoma. Experimental: Red clover lyophilized powder (CAS = 85085-25-2) with a fixed ratio of Formononetin, Biochanin A, Daidzein, and Genistein was acquired from Sigma Aldrich German company. Raji cells were obtained from the Pasteur Institute of Iran-Tehran. Raji cells were treated with different concentrations of RCE, and viable cells were measured at an interval of 24, 48, and 72 hours incubation in three days by MTT assay. Agarose gel electrophoresis was used to determine the DNA degradation. Annexin V-FITC/PI kit and flow cytometry assay were used to determine the percent of apoptotic and necrotic treated Raji cells. Also, expression changes in cMYC, ID3, and P53 genes were measured by real-time PCR. Results: Red clover extract can prevent in vitro proliferation of the Raji cells in a time and dose-dependent manner. RCE, as well as c-MYC gene suppression and induction of ID3 and P53 genes, enters the Raji cells in the apoptosis stages with an acceptable percentage and has complication cure potential in Burkitt's lymphoma. Recommended applications/industries: The extract used in this study combines four components. The individual evaluation effects of Formononetin, Biochanin A, Daidzein, and Genistein on Raji cells are recommended.